PERAN KLASIFIKASI INFORMASI DALAM BIG DATA DI PERPUSTAKAAN - Mahadewi, Ni Putu Tisna; Ginting, Richard Togaranta; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2024)
This article discusses the important role of classification in big data in libraries with the aim of knowing and understanding the important role of classification in libraries, especially in managing big data in libraries. The method used in this research is a literature study that utilizes literary sources. The results of this research include implementing an effective classification system which is very important to optimize information access, support information retrieval systems, and improve library services both in terms of quality and to be ready to face the challenges of the explosion of data in libraries.